Study on dynamic characteristics of the temperature and stress field in induction and laser heating for the semi-infinite body. Issue 4 (3rd April 2018) - Chen, Guohua; Liao, Ridong
ABSTRACT: This study analyzed the dynamic characteristics of temperature and stress fields during induction and laser heating of a semi-infinite body. The semi-infinite body was subjected to a distribution heat flux (induction heating) at a particular depth range and then to a surface heat flux (laser heating). Using the Green function method and the Laplace transform, the temperature and stress fields solutions were acquired for both heating methods. The analytical results of the temperature and stress fields are shown graphically in the time domain for a selected position. It was found that under the same input power conditions, the temperature field acquired is identical in both induction and laser heating in the range of more than one skin depth. The peak dynamic thermal stress from both heating methods increases rapidly along the depth, and converges to a fixed value. Meanwhile, the peak thermal shock stress is relatively small, and quickly decays at a certain position in a very short duration. Therefore, the thermal shock dynamic characteristics are negligible in the two highly variant transient heating methods—induction and laser.